The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1563/aaid-joi-d-17-00101
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With the Use of Recombinant Human Bone Morphogenic Protein–2 in Ridge Augmentation: A Case Report

Abstract: This case report aims to describe in detail a complication associated with resorption of regenerated bone following implant placement and ridge augmentation using recombinant human bone morphogenic protein-2 (rhBMP-2) in combination with allograft and xenograft. Bilateral maxillary sinus and ridge augmentation procedures were completed using rhBMP-2 combined with allograft and xenograft. Five months later, significant bone augmentation was achieved, which allowed for the placement of 4 implants. Upon stage 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It was previously reported that the addition of autologic osteoblasts to biomaterials promoted new bone formation, and increased levels of growth factors such as bone morphogenetic protein 2 (BMP-2) (14,15). However, the short-lived in vivo efficacy of BMP-2 and the difficulty of osteoblast isolation limits their usage (16,17). Recent studies have therefore focused on the combination of osteogenic gene-modified mesenchymal stem cells (MSCs) and BCPs for TEBGs, and an important goal is to identify the most effective osteogenic genes in this process (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that the addition of autologic osteoblasts to biomaterials promoted new bone formation, and increased levels of growth factors such as bone morphogenetic protein 2 (BMP-2) (14,15). However, the short-lived in vivo efficacy of BMP-2 and the difficulty of osteoblast isolation limits their usage (16,17). Recent studies have therefore focused on the combination of osteogenic gene-modified mesenchymal stem cells (MSCs) and BCPs for TEBGs, and an important goal is to identify the most effective osteogenic genes in this process (18,19).…”
Section: Introductionmentioning
confidence: 99%